Spent Epoxy Molding Compound as Cement Replacement in Lightweight Concrete - Abdul Hafiz, Muhammad Faqhrul Haiqal; Harun, Hasnida (Progress in Engineering Application and Technology, 2026)
The increasing demand for sustainable development in the construction industry has spurred interest in utilizing industrial waste materials. This study investigates the potential of incorporating EMC as a partial replacement in concrete, aiming to reduce cement usage by partially replacing it with EMC to enhance environmental sustainability. The main objective of this research is to evaluate the effects of different EMC replacement ratio (0%, 2.5, 5% and 7.5%) on the mechanical properties and workability of concrete. The methodology involves preparing concrete mixes with varying proportions of EMC as a partial replacement for cement. Standard tests were conducted to assess the concrete’s workability, as well as its mechanical properties through compressive strength, water adsorption, thermal conductivity and density tests at 7 and 28 days of curing. Based on mechanical, durability, density, and thermal performance 2.5% EMC replacement was determined to be the optimal EMC-to-cement ratio for LPUC. This mix demonstrated a balanced performance, with compressive strength similar to the control mix, along with the advantages of reduced density and enhanced durability. The anticipated strength development trend was observed at both 7 and 28 days of curing, in accordance with BS EN 12390-3, indicating that low EMC replacement does not significantly interfere with the cementitious bonding or hydration process.